2013
DOI: 10.5539/ijc.v5n4p103
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Conditions and Phytochemical Screening of Root Extract of Synadenium glaucescens Pax

Abstract: Optimization of extraction conditions and phytochemical screening of the root bark of Synadenium glaucescens were carried out in a stepwise manner in order to obtain the highest yields and the constituents of the extracts. Sequential extraction using Soxhlet method was performed using dichloromethane, hexane and petroleum ether, respectively, each followed by ethanol. Extraction conditions included: running time of 2 to 6 hours, temperature at 25 o C to 95 o C and particle size ranging from 0.4mm to >3mm diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
1
11
0
3
Order By: Relevance
“…Contrary to the use of dichloromethane which was an organic solvent, no bacterial activity has also been observed. That was in accordance with previous work of Mabiki et al (2013) that showed for the most of part of terpenes/terpenoids compounds in dichloromethane extract. It was known that because of this chemical diversity, terpenes/terpenoids have great industrial uses as flavors, fragrances (Schwab et al, 2008), high grade lubricants, biofuels, agricultural chemicals and in the near future will play a more significant role in medicines (Niehaus et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…Contrary to the use of dichloromethane which was an organic solvent, no bacterial activity has also been observed. That was in accordance with previous work of Mabiki et al (2013) that showed for the most of part of terpenes/terpenoids compounds in dichloromethane extract. It was known that because of this chemical diversity, terpenes/terpenoids have great industrial uses as flavors, fragrances (Schwab et al, 2008), high grade lubricants, biofuels, agricultural chemicals and in the near future will play a more significant role in medicines (Niehaus et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…Ningsih (2016) menambahkan bahwa maserat yang berasal dari serbuk memiliki kandungan fitokimia yang lebih tinggi dibandingkan dengan maserat yang berasal dari bahan. Hal ini berkaitan dengan luas permukaan yang kontak dengan pelarut, dimana serbuk memiliki luas permukaan yang lebih besar untuk kontak dengan pelarut sehingga dimungkinkan lebih banyak senyawa-senyawa yang termaserat (Maslukhak et al, 2016;Mabiki et al, 2013;Baldosano et al, 2015).…”
Section: Nilai Organoleptikunclassified
“…Oleh karena itu, salah satu cara untukmempertahankan kesegaran ikan adalah dengan membuang sumber-sumber bakteri, salah satunya adalah insang (Junianto, 2003). Perbedaan nilai organoleptik insang yang direndam maserat serbuk buah dan buah mangrove dikarenakan maserat serbuk buah memiliki kandungan fitokimia yang lebih tinggi karena berkaitan dengan luas permukaan bahan yang kontak dengan pelarut sehingga berdampak pada lebih banyaknya senyawa-senyawa yang termaserat (Maslukhak et al, 2016;Mabiki et al, 2013;Baldosano et al, 2015).…”
Section: Nilai Organoleptikunclassified
“…Some attempts including the use of liquid/liquid extraction with dichloromethane (DCM), which have shown to improve yield [22] and remove non-polar compounds from the extract [23], although producing lower antioxidative properties in some cases [23]. Related organic solvents such as n-hexane has shown to yield minimal extracts of M. palustris with little to no antioxidative properties [21].…”
Section: Extraction and Downstream Processingmentioning
confidence: 99%